Assessing the Impact of Current Business Practices on Value-Added Value Propositions (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In today's dynamic business landscape, organizations face ever-increasing challenges in creating and maintaining a competitive advantage. One essential factor in achieving this advantage is the development and execution of value-added value propositions (VVPs). This scientific article explores the impact of current business practices on VVPs, examining the strategies and trends that shape these propositions and their implications for businesses in various industries.